How Are Government Hospitals Performing? A Study of Resource Management in DOH-retained Hospitals - Rouselle F. Lavado; Abigail Barbara Sanglay-Dunleavy; Yasuhiko Matsuda; Jeanette F. Jimenez (Philippine Institute for Development Studies (PIDS), 2010)
The paper attempts to provide an overview of the hospital sector in the Philippines with particular emphasis on hospitals being managed by the DOH. The paper begins with an overview of the hospital sector in the Philippines, describing the size, location, and utilization of hospital services. To assess the efficiency and effectiveness of service delivery in DOH-retained hospitals, an analysis of resource management is undertaken by examining the sources of funds, planning and budgeting cycle, uses of funds, and monitoring set-up. The paper provides a critique of recent policies concerning hospitals as outlined in the Health Sector Reform Strategy. The last section concludes and provides some policy recommendations.
Keywords: 330; health sector; health expenditures; health care; health facilities; hospitals; health care reform; health care financing; health management; health service delivery; Philippines; health; health funds; Krankenhaus; Krankenhausfinanzierung; Gesundheitsreform; Gesundheitsversorgung; Philippinen